Convective Heat Transfer Enhancement for Electronic Device Applications Using Patterned MWCNTs Structures. Issue 9 (12th June 2016) - Shahzad, M. I.; Giorcelli, M.; Ventola, L.; Perrone, D.; Shahzad, N.; Chiavazzo, E.; Asinari, P.; Cocuzza, M.; Tagliaferro, A.
Abstract : This article reports on the heat transfer characteristics of columnar, vertically aligned, multiwall carbon nanotubes grown on a patterned Si surface. In the first part, we describe the procedure for patterning the silicon (Si) surface and the growth of multiwall carbon nanotubes (MWCNTs) on these patterned surfaces. The diameter of MWCNTs grown by chemical vapor deposition technique was in the range of 30–80 nm. In the second part, structures mimicking macroscopic finned heat sinks are used for enhancing forced convective heat transfer on a silicon substrate. Convective heat transfer coefficient has been experimentally measured for silicon substrates with and without MWCNT-based fins on it. The configuration with MWCNTs based fins shows an enhancement in convective heat transfer of 40% and 20%, as maximum and average value, respectively, compared to the bare silicon. Experiments have been carried out in a wind tunnel with air as coolant in fully turbulent regime. These encouraging results and the possibility of growing structures directly on silicon can be regarded as a first step.